Septooptic Dysplasia with an Associated Arachnoid Cyst - Skyler V. McLaurin-Jiang; Julie K. Wood; David F. Crudo (Case Reports in Pediatrics)
A 4-week-old male infant presented with hypothermia, hypoglycemia, and hyperbilirubinemia. His medical history was remarkable for hydrocephalus secondary to an arachnoid cyst, intermittent hypoglycemia, hypothermia, and poor feeding requiring nasogastric tube for nutrition. Physical exam revealed retrognathia, mild hypotonia, micropenis, and clinodactyly. Ophthalmologic exam demonstrated bilateral optic nerve hypoplasia (ONH). Laboratory data confirmed inadequate cortisol and growth hormone response to hypoglycemia, a low thyroxine level, and direct hyperbilirubinemia. Magnetic resonance imaging of the brain confirmed the known history of arachnoid cyst with hydrocephalus but also revealed anterior pituitary hypoplasia, absence of the posterior pituitary bright spot, a thin pituitary stalk, and bilateral optic nerve hypoplasia. A diagnosis of septooptic dysplasia (SOD) was made. Hormone replacement with hydrocortisone and levothyroxine was started with improvement in the infant’s glycemic control, thermoregulation, feeding, and cholestasis. This case reinforces the importance of careful physical examination and laboratory review in a patient with known history of arachnoid cyst which has been previously described as an associated feature of optic nerve hypoplasia and hypopituitarism.